Testing Nigeria’s Marginal Propensity to Consume (MPC) Within the Period 1980-2004 - J.B. Tsenkwo (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2011)
The study is an attempt to gauge Nigeria’s marginal propensity to consume (MPC),and average propensity to consume(APC).Relevant variables were identified and data on them obtained spanning from 1980-2004.The econometrics methodology of unit root, and co integration were used to determine the stationary and the long run relationship among the variables. The computation of MPC and APC were carried out using the nominal data obtained from the identified variables. The results of MPC and APC conform to Keynes proposition that is less the one and stable, however our results for MPC though less than one and stable exhibit the tendency to grow above one. This has serious policy implications for saving, capital formation, and investment on whole. The author therefore suggest for a policy to discourage consumption and encourage production.